2021
DOI: 10.1371/journal.pone.0257833
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and contextual factors associated with compassion fatigue among nurses in northern Uganda

Abstract: Background Compassion fatigue is associated with negative consequences that undermine workplace performance. However, literature is scarce on compassion fatigue among nurses in the context of Uganda who are at higher risk of compassion fatigue owed to the nature of their occupation and the unfavorable work environment. We aimed to assess the prevalence and predictors of compassion fatigue among nurses in Northern Uganda. Methods We conducted a cross-sectional survey among 395 randomly selected nurses from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Likewise, a study revealed that more than half of the studied sample had an average level of ProQoL components (CS, BO, STS). [ 22 ] While a study conducted in Northern Uganda,[ 23 ] reported that 49.11% of nurses had a high level of compassion fatigue and a study in Malaysia reported a high level of burnout among 39.4% of nurses. [ 5 ] This could be because nurses are primary contacts, spend more time with patients regularly, and work under high stress during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a study revealed that more than half of the studied sample had an average level of ProQoL components (CS, BO, STS). [ 22 ] While a study conducted in Northern Uganda,[ 23 ] reported that 49.11% of nurses had a high level of compassion fatigue and a study in Malaysia reported a high level of burnout among 39.4% of nurses. [ 5 ] This could be because nurses are primary contacts, spend more time with patients regularly, and work under high stress during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed higher rate of compassion fatigue 7,8 and burnout 6,7 among nurses during COVID-19 pandemic. The constant exposure to crisis causes mental and physical tiredness 4 and burnout 6 as well as reduces the work efficiency and quality of work and patients' disease recovery.…”
Section: Introductionmentioning
confidence: 98%
“…In particular, professionals working in cancer care are exposed to exact a toll on their physical and emotional health [1]. Compassion fatigue reduced the practitioner's capacity to be empathic or bear the suffering of clients [2][3][4][5][6]. On the other hand, compassion satisfaction reflects the rewards of caring for others and counterbalances the risks of compassion fatigue [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%